The Role of Digital Banking and Fintech in Advancing Financial Inclusion - Sihotang, Daniel Janrian; Kamaludi, Elvin; Indriani, Farida (Economic and Business Horizon, 2025)
This study examines the role of digital banking and fintech in promoting financial inclusion and sustainable economic growth within a globalized context. As technological innovations transform financial services, key questions focus on how fintech bridges gaps in access, enhances efficiency, and drives economic participation among underserved populations. The research analyzes data from various countries to assess the effectiveness of fintech initiatives in expanding financial access, highlighting successful strategies and common challenges such as regulatory barriers, security risks, and digital literacy gaps. The discussion explores strategies for effective implementation, including collaboration among regulators, financial institutions, and technology providers, as well as the importance of establishing a secure digital infrastructure. Results indicate that fintech solutions significantly improve access to banking, especially in rural and low-income areas, contributing to economic resilience and social inclusion. The article emphasizes that a supportive policy environment and innovative technological deployment are essential for maximizing fintech's impact on economic sustainability. Findings suggest that targeted efforts to address barriers can foster greater financial inclusion, thus supporting broader goals of economic growth and development. Overall, the study underscores the potential of fintech to serve as a catalyst for inclusive, sustainable financial ecosystems in a rapidly globalizing world.